Geometric Patterns in Jaipong Dance: An Ethnomathematics Study - Lestari, Santi Arum Puspita; Kusumaningrum, Dwi Sulistya; Nurapriani, Fitria (Universitas Wiralodra, 2024)
Jaipong dance is a traditional dance deeply rooted in the culture of West Java. However, not everyone is aware that Jaipong dance incorporates mathematical elements into its performance. Therefore, the aim of this research is to analyze mathematical concepts, particularly geometric patterns, within Jaipong dance. The research approach employed is ethnography, with data analysis including domain analysis, taxonomic analysis, and ethnographic analysis. Data was collected through three main methods: interviews, observations, and documentation. The research findings reveal the utilization of mathematical concepts in Jaipong dance. This includes counting from 1 to 8 to maintain the dance's rhythm and the use of geometric shapes in floor patterns. The floor patterns in Jaipong dance reflect the spatial arrangement used in the dance performance. Some of the floor patterns used in Jaipong dance encompass straight lines, diagonals, triangles, quadrilaterals, and pentagons. Thus, Jaipong dance not only blends artistic movements but also integrates mathematical and geometric concepts within its floor patterns. Geometry plays a significant role in creating visual aesthetics and regulating interactions among the dancers during Jaipong dance performances.